1997
DOI: 10.1111/j.1600-0838.1997.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle phosphocreatine repletion following single and repeated short sprint efforts

Abstract: Phosphocreatine (PCr) repletion following either single (1x6 s, n=7) or repeated (5x6 s, departing every 30 s, n=8) maximal short sprint cycling efforts was measured in separate groups of trained subjects. Muscle biopsies (vastus lateralis) were taken pre‐exercise before warming up, and then at 10 s, 30 s and 3 min post‐exercise. After the 1 × 6 s sprint PCr concentration was respectively, 55% (10 s; P<0.01), 69% (30 s; P<0.01) and 90% (3 min; NS) of the pre‐exercise value (mean±SD) (81.1±7.4 mmol · kg−1 DM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 21 publications
5
99
1
9
Order By: Relevance
“…shuttle distances and a short or non-existent rest period resulting in a lack of phosphocreatine (PCr) resynthesis or lactate clearance (26). It may be these issues which contribute to the v20SRT being lower than that found in the 12-min Cooper run …”
Section: The 30-15 Intermittent Fitness Testmentioning
confidence: 72%
See 1 more Smart Citation
“…shuttle distances and a short or non-existent rest period resulting in a lack of phosphocreatine (PCr) resynthesis or lactate clearance (26). It may be these issues which contribute to the v20SRT being lower than that found in the 12-min Cooper run …”
Section: The 30-15 Intermittent Fitness Testmentioning
confidence: 72%
“…Furthermore, 15s recovery may allow for sufficient but incomplete restoration of energy substrates such as phosphocreatine (26). The 40m shuttle distance is thought to aid in reducing blood lactate levels compared to the more common 20m…”
Section: The 30-15 Intermittent Fitness Testmentioning
confidence: 99%
“…Por outro lado será necessário considerar que a duração do esforço no Line-drill Test implica solicitações metabólicas que envolvem, pelo menos em parte, a produção anaeróbica de ATP pela degradação de PCr e glicólise anaeróbica 28 . A relevância do metabolismo anaeróbico no Line-drill Test foi evidente na associação observada com uma prova anaeróbica de 30 s em cicloergómetro em jogadores de basquetebol adolescentes 6 .…”
Section: Discussionunclassified
“…Gaitanos et al (1993) detected that after a single 6-s maximal cycle sprint, there was a 57% decline (76.5 ± 7.2 to 32.9 ± 2.6 mmol kg -¹) in muscle PCr concentrations. Similarly, Dawson et al (1997) found that after one maximal 6-s cycle sprint, PCr stores were at 55%, 69%, and 90 % of the pre-exercise value at 10-s, 30-s, and 3 minutes post-exercise, respectively. In addition, a comparison was made on the influence of one single maximal cycle sprint (1 x 6-s) vs. a repeated series of cycle sprints (5 x 6-s) on PCr depletion and repletion rates.…”
Section: Fatigue Specific To a Common Isokinetic Knee Strength Testinmentioning
confidence: 99%
“…Such an occurrence was the eventual outcome in the findings of Dawson et al (1997) and Gaitanos, Williams, Boobis, & Brooks (1993). Gaitanos et al (1993) detected that after a single 6-s maximal cycle sprint, there was a 57% decline (76.5 ± 7.2 to 32.9 ± 2.6 mmol kg -¹) in muscle PCr concentrations.…”
Section: Fatigue Specific To a Common Isokinetic Knee Strength Testinmentioning
confidence: 99%